Versatile BiFeO3 shining in piezocatalysis: From materials engineering to diverse applications - Jian Dai; Zhenhao Fan; Hang Xie; Yitao Jiao; Fu Huang; Ahmad Azmin Mohamad; Yunfei Chang; Yangke Long; Dawei Wang (Journal of Advanced Ceramics)
The growing global demand for sustainable solutions to address energy and environmental challenges has spurred significant interest in catalytic technologies. Piezocatalysis has emerged as a sustainable technology for environmental remediation and energy conversion because of its unique characteristics of harvesting mechanical energy into electrochemical energy. Versatile BiFeO3 (BFO) stands out among a range of piezocatalysts for its distinctive integration of piezoelectric, multiferroic, and optical properties. This review critically examines piezocatalytic mechanisms, including energy band theory, screening charge effects, and displacement current theory, revealing the intricate roles of internal charges, screening charges, and piezoelectric electrons in driving catalytic reactions. Furthermore, the evolution of BFO-based piezocatalysis is systematically reviewed, emphasizing its structural characteristics, representative synthesis methods, performance optimization strategies, and diverse applications, such as organic pollutant degradation, H2 production, H2O2 generation, CO2 reduction, and sterilization. In particular, the underestimated ferroelectric polarization effect of BFO on CO2 reduction is critically analyzed and elaborated. This review identifies critical challenges and outlines future research directions to advance high-efficiency BFO-based piezocatalytic systems. Overall, this comprehensive analysis underscores the potential of BFO in piezocatalysis, bridging materials engineering with practical applications and offering insights into future advancements.